KINERJA PEGAWAI BADAN NARKOTIKA NASIONAL (BNN) PROVINSI RIAU DALAM PELAKSANAAN OPERASI PEMBERANTASAN DI KOTA PEKANBARU - Abdul Rahman; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the performance of organized the organization, BNNP have obstacles in carrying out duties and obligations, the most important is the number of existing employees in the BNNP. The number of existing employees in the Riau BNNP only 62 employee, including members of the National Police. Thus shows that the number of employees of BNNP Riau can affect the performance of employees. The purpose of this research is to analyze the performance of the employees of the National Narcotics Agency (BNN) Riau Province in the implementation of the eradication Operation in the city of Pekanbaru and also to find out the factors restricting factors performance of employees. The measurement of performance indicators used theory of Mangkunegara (2009) consisting of quality, quantity, cooperation, initiative, skills, and responsibilities. The research method used was qualitative research with the descriptive approach.The results showed that; 1) By indicators of quality, doing a network mapping narcotics carefully it is successfully eradication operations. 2) By quantity indicator, each times an operation involving a combined force of the eradication team. 3) By indicators of cooperation, eradication operations involving cooperation with military personnel, Riau Police, TNI Provost, Satpol PP and helped by community. 4) By indicators of initiative, prioritizes the intelligence teams already highly proficient and experienced. In addition many of the employees who have the initiative to bring additional equipment and infrastructure to support operational standards eradication. 5) By indicators of skills, eradication operations are supported by employees who have high proficiency in terms of experience, skill, discipline, work and achievements. 6) By indicator of responsibility, all the employees work in accordance with the duties and responsibilities of each position are contained in the decision of the head of the BNN about the revision of the list order of employees in Environmental Regulation, and also of the BNN BNN number 3 was 2015, about the organization and governance of work BNN for city level. 7) The restricting factors performance of employees BNN Riau Province in the implementation of the eradication Operation in the city of Pekanbaru consists of knowledge, skills, and attitude/behavior of the employees.Keywords: Quality, quantity, cooperation, initiative, skills, and responsibilities